THE EFFECT OF AN ORGANIZED HEART FAILURE PROGRAM ON THE RATE AND TIME TO FIRST READMISSION IN PATIENTS DISCHARGED WITH A DIAGNOSIS OF ACUTE DECOMPENSATED HEART FAILURE ADMITTED TO CARDIOLOGY DEPARTMENT, AYUB TEACHING HOSPITAL, ABBOTTABAD - Saad Shams; Muhammad Imran Khan; Fatima Javed; Rakhshanda Afsar; Zia Ullah Khan; Aftab Ahmad; Mati Ullah Khan (Journal of Ayub Medical College Abbottabad, 2024)
Background: Heart Failure (HF) is globally recognized as one of the major causes of morbidity and mortality as it has severe lasting impacts on quality of life, healthcare finances, and survival. Keeping in view the poor prognosis associated with ADHF admissions, structured heart failure programs can enhance treatment adherence, foster better self-care, and lower the rate of readmissions. This study was carried out to evaluate the impact of a structured heart failure program on the readmission rates and clinical outcomes of patients with acute decompensated heart failure at Ayub Teaching Hospital, Abbottabad. Methods: 30 patients were recruited in this longitudinal study as per the inclusion criteria; aged between 20 to 80 years, within 7 days of their discharge, and followed for 20 weeks in a specialized heart failure clinic, with regular follow-ups, guideline-directed medical therapy (GDMT) optimization and patient education. Results: Out of the 30 patients enrolled (mean age 65.26 years; 53% male) with a history of 2 prior admissions for acute decompensated heart failure (ADHF) in the last 6 months, 24 completed the program. GDMT adherence improved significantly, with beta-blocker usage reaching 100%. The unscheduled readmission (defined as unscheduled visit for worsening heart failure resulting in admission) for worsening heart failure or all cause death rate was 13%.There were no deaths recorded due to worsening heart failure. NT-proBNP levels declined notably, and ejection fraction improved or remained stable for most of the patients. Approximately 23% of the patients were classified as NYHA class I at baseline, which improved to 67% at the final visit. Conclusion: This pilot study demonstrated that a structured heart failure program improved clinical outcomes in terms of unscheduled admissions or deaths due to worsening heart failure underscoring the need for establishing specialized multidisciplinary heart failure clinics. Keywords: Heart Failure program; Acute Decompensated Heart failure; GDMT